Circular economy as the basis of today's sustainable development - Janković Gordan; Golubović Miloš (Održivi razvoj, 2025)
The circular economy is defined as a quot systematic approach to economic development designed to benefit businesses, society and the environment quot. Unlike the linear economy, which operates on the principle of quot take-make-discard quot the circular economy is regenerative by design and aims to make the development of the economy indifferent to the limitations of resources that exist in nature. Conceptually speaking, the circular economy is closely related to sustainable development. It represents a narrower concept, and by achieving its goals, it simultaneously contributes to achieving the goals of sustainable development. Considering the ecological situation that exists in the world and the dynamics of spending limited resources through economic progress, the circular economy is emerging as a concept that potentially offers a solution to the difficult situation in which humanity finds itself. Nevertheless, despite numerous examples of successful practice, both at the level of individual economic actors and at the level of entire economic systems, the idea of circular economy has not yet fully taken root and is waiting for complete affirmation in practice. The reason for this lies in numerous limitations of a social, systemic and financial nature. The aim of this paper is to point out the unsustainability of the existing concept and to highlight the idea of a circular economy to the general public as an imperative for the survival of modern society.